Assessing the Need for Applying Multimodal Speed Distribution in Road Transport Macro Emission Estimation - Török, A.; Zefreh, M. Maghrour (Acta Technica Jaurinensis, 2016)
Vehicles speed distribution is an important input parameter in lots of issues, such as kinematical traffic simulation model, road design, speed limit evaluation, road traffic noise prediction or vehicles emission estimation. In this paper, a new approach has been presented in which the speed is randomly generated according to different speed distributions. Later on, these distributions were used as the basis of emission estimation. These different distributions were chosen according to the contextual traffic situation (free flow, pulsed accelerated flow, intersection, congestion, etc.) and were assigned to the fundamental diagram. The study of the effect of different speed distributions on the resulting emission level has been performed. The considerable difference in the emission models related to Log-normal distribution as well as exponential, chi-square and equal distribution to normal Gaussian distribution implies that these different traffic conditions will have a considerable effect on emission and will show the need for applying multimodal speed distribution in macro emission estimation rather than unimodal distribution. It should also be mentioned that this result may lead to the chance of revising the simulation software in further studies